STRATEGI PENINGKATAN MUTU PEMBELAJARAN BAHASA ARAB DI PONDOK MODERN - Ariska Kusuma Wardani; Danial Hilmi (Bajang Institute, 2021)
Arabic is a language that every Muslim must learn. When Islam entered and developed in Indonesian society, Arabic played a role as a bridge for scholars with previous books to provide Islamic teachings with the translation method. Having the ability and ability to speak Arabic is very beneficial, not only for scholars but also students who will later become politicians and financiers, so that a synergy between power and science is achieved which eventually turns into a great force in the development of the Islamic religion. One of the organizations that demands to learn Arabic is the Islamic Boarding School which is now undergoing modernization. This study aims to examine Arabic teaching strategies to improve the quality of Arabic learning at the Babussalam Alfirdaus Islamic Boarding School. The results show that in improving the quality of Arabic learning at the Babussalam Alfirdaus Islamic Boarding School, an introduction is carried out by providing new vocabulary every morning, applying new vocabulary in daily activities, getting used to the use of Arabic both verbally and in writing, conducting periodic tests and taking action. students who do not use Arabic according to applicable rules